DIGITAL MARKETING DAN BRANDING: KUNCI PEMBERDAYAAN DAN PENINGKATAN UMKM DI ERA DIGITAL KELEMBAGAAN BUMDES WORI, MINAHASA UTARA, SULAWESI UTARA. - Lidia Aprileny Hutahaean; I Kadek Satria Arsana; Dominikus Rojoki Manullang; Vinda Afnita; Sahat Renol HS; Selvita Eka Eviana Purba; Tiara Lestari Paembonan (Publikasi Kegiatan Pengabdian Masyarakat Widya (PUNDIMASWID), 2025)
This Community Service Program (Pengabdian kepada Masyarakat/PkM) aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) and Village-Owned Enterprises (BUMDes) in Wori Village, North Minahasa Regency, through the strengthening of digital marketing and product branding based on village institutional development. Wori Village has significant tourism potential, supported by coastal landscapes, mangrove forests, and flagship destinations such as Mangrove Park Ecotourism and the 3D Bridge, which provide strategic opportunities for the development of local MSMEs. However, this potential has not yet been optimally utilized through digital-based marketing strategies and systematic brand development. The program employed an integrated training and mentoring approach conducted in three stages: the preliminary stage (needs assessment and problem identification), the implementation stage (digital marketing and branding training with hands-on practice), and the evaluation stage. The approach was grounded in institutional theory, digital marketing theory, and community empowerment theory, positioning BUMDes as a key institution in coordinating and supporting collective marketing efforts among MSMEs. The results indicate a significant improvement in participants’ understanding and skills in utilizing digital media for product promotion, developing brand identity for local products, and increasing confidence in accessing wider markets. Furthermore, the program strengthened the role of BUMDes as a facilitator of community economic empowerment by integrating tourism potential with MSME development. Overall, this Community Service Program contributes to improving MSME competitiveness and fostering sustainable village economic development in the digital era. Keywords: MSMEs, BUMDes, digital marketing, branding, village tourism, community service.